ANALISIS PENGELOLAAN TURAP 11-14 ULU DI KOTA PALEMBANG - Ratih Baniva; Aprilianda (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2022)
The sheet pile 11-14 Ulu which is located on the banks of the Musi River in Palembang City was built in 2014 and is still functioning and no further sheet pile management has been carried out. This is a challenge for the government in managing sheet pile so that it can make an optimal positive contribution to construction. The purpose of this study was to identify the management status and analyze the level of damage to the structural components of 11-14 Ulu sheet piles in Palembang City. This research is a quantitative descriptive study where this research was conducted using a survey method. From the results of the analysis, it is found that the identification of sheet pile management is the authority of the Central Sumatra VIII River Basin. The level of damage that occurs to the structural components of pile caps, piles, floor plates and fence columns with a percentage of damage less than 10% is in good condition. Slightly damaged conditions occurred in sheet pile structural components by 10,39% and stairs by 19,70%. Based on the level of damage, it can be categorized as preventive maintenance because the percentage of damage that occurs is still below 30%. Abstrak Turap 11-14 Ulu yang berada di tepian Sungai Musi Kota Palembang dibangun pada tahun 2014 hingga saat ini masih berfungsi dan belum diadakan pengelolaan turap lebih lanjut. Hal ini merupakan tantangan bagi pemerintah dalam mengelola turap sehingga dapat memberikan kontribusi positif yang optimal dalam pembangunan. Tujuan dari penelitian ini adalah mengidentifikasi status pengelolaan dan menganalisis tingkat kerusakan pada komponen struktur turap 11-14 Ulu di Kota Palembang. Penelitian ini merupakan penelitian deskriptif kuantitatif dimana penelitian ini dilakukan dengan metode survei. Dari hasil analisis maka didapat identifikasi status pengelolaan turap merupakan wewenang Balai Besar Wilayah Sungai Sumatera VIII. Tingkat kerusakan yang terjadi pada komponen struktur pile cap, tiang pancang, plat lantai dan kolom pagar dengan persentase kerusakan kurang dari 10% dalam kondisi baik. Kondisi rusak ringan terjadi pada komponen struktur sheet pile sebesar 10,39% dan tangga sebesar 19,70%. Berdasarkan tingkat kerusakan dapat dikategorikan sebagai pemeliharaan preventif karena persentase kerusakan yang terjadi masih dibawah 30%.